First European quality of life survey: time use and work-life options over the life course - Torres, Anália (2010)
This report addresses the key issue of time use and work–life options over the life course. The report aims to contribute to current debates on the subject, placing them in the wider context of 25 European countries and viewing them from a life course perspective. It considers the ways in which the institutional and policy framework can be expected to affect actual and preferred patterns of time use over the life course, focusing on distinct stages of the life course. It investigates individuals’ views on available working time options, while exploring their preferences regarding measures designed to help them reconcile their different time-demanding commitments.